THE EFFECT OF SOCIAL SUPPORT ON PRISONERS EMOTIONAL CONTROL AT CLASS IIA PEMATANGSIANTAR CORRECTIONAL INSTITUTION - Silalahi, Jhon Philip Extrada; Rachmayanty, Rachmayanty (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study is based on the influence of social support on emotional control of prisoners at the Class IIA Pematang Siantar Penitentiary, which in several aspects is found to be concerned about the emergence of security and order disturbances due to the inability to control emotions. Employee work involvement is needed to support this study, while the trigger for negative emotions of prisoners is through the environment and officers around them. This study aims to determine the effect of social support on emotional control of prisoners at the Class IIA Pematang Siantar Penitentiary. The research method used is a quantitative method with a descriptive research type. The researcher used a sampling technique, namely simple random sampling, which then obtained 230 respondents. There are 35 statement items distributed using a questionnaire data collection technique. The data analysis techniques used are the normality test, simple linear regression test, significance test, and determination test, which are then processed using SPSS version 27. The results of the study showed that there was an influence between transformational leadership and work involvement. The results of the determination test show that the influence of social support has a positive influence of 37.5% on the emotional control of prisoners at the Class IIA Pematang Siantar Penitentiary. Keywords: Social Support; Emotional Control; Influence; Disturbance of Public Order